2007
DOI: 10.1007/s10750-007-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diazinon on life stages and resting egg hatchability of rotifer Brachionus plicatilis

Abstract: This paper has not been submitted elsewhere in identical or similar form, not will it be during the first three months after its submission to Hydrobiologia. showed that among the life history parameters, the time the rotifers took to release neonates is the most sensitive, giving the lowest EC 50 value of 1.24 mg/L. The fecundity of maternal females, amictic and mictic daughters was also investigated. Rotifers exposed to 10.0 mg/L produced significantly fewer amictic daughters, and at this concentration, roti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 22 publications
2
9
0
2
Order By: Relevance
“…This study showed that even though amictic females reproduced normally in the presence of low concentrations of atrazine and carbaryl, viability of resting eggs was severely affected. The vigor of resting eggs of B. plicatilis exposed to low concentrations of diazinon also produced similar results (Marcial and Hagiwara 2007). Thus, the viability of resting eggs is an ecologically key index for assessing effects of pollutants on the reproduction of rotifers and others.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…This study showed that even though amictic females reproduced normally in the presence of low concentrations of atrazine and carbaryl, viability of resting eggs was severely affected. The vigor of resting eggs of B. plicatilis exposed to low concentrations of diazinon also produced similar results (Marcial and Hagiwara 2007). Thus, the viability of resting eggs is an ecologically key index for assessing effects of pollutants on the reproduction of rotifers and others.…”
Section: Discussionsupporting
confidence: 54%
“…These results show that sexual reproduction is more sensitive than asexual reproduction when rotifers are exposed to atrazine and carbaryl. Several investigations using the rotifers B. calyciPorus and B. plicatilis also found this phenomenon when rotifers were exposed to pesticides and steroid hormones (Snell and Carmona 1995;Preston et al 2000;Preston and Snell 2001;Marcial and Hagiwara 2007;Snell and DesRosiers-noac 2008). Thus, rotifers may be used as biomarkers for the presence of endocrine-disrupting chemicals in the environment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…储朝霞等对轮虫生活史特征的影响的研究也表明轮虫的胚胎发育时间和幼体阶段会受到草甘 膦的影响 [5] . Marcial等对褶皱臂尾轮虫生活史参数如产第一枚卵的时间和第一枚卵孵化时间、 生殖期以及 平均寿命的研究发现, 当敌匹硫磷的浓度达5mg/L时会延迟其产卵时间, 暴露于2.5mg/L或更高浓度第一 次产幼时间比对照组延迟, 平均寿命也受到影响, 十指臂尾轮虫平均生命跨度、平均寿命都受到铅离子 浓度水平、混浊度以及二者之间相互作用的影响 [7][8] .…”
Section: 图1 不同浓度氰戊菊酯(A)和tbtc(b)处理后萼花臂尾轮虫总产卵量unclassified
“…育观察结果相反, 其实验结果认为在褶皱臂尾轮虫各生活史参数中, 第一枚卵的孵化时间(即胚胎发育时 间)最敏感 [8] . 且与对照组比较TBTC的生殖前期历时延长, 即幼体发育阶段延长, 生殖期和生殖后期历时 缩短, 平均寿命也缩短.…”
Section: 许多水生生物种的早期生命阶段对毒物的敏感性较晚期发育阶段高 胚胎发育(生活史的第一阶段)unclassified